A POLICY IN ELEVATING THE EDUCATIONAL QUALITY IN INDONESIA THROUGH THE APPLICATION OF GOOD UNIVERSITY GOVERNANCE PARADIGMS - KRISTIANTY, THERESIA (PPs UNJ, 2012)
The core meaning of good university governance is that the university as an open system, reluctanly or not has to follow the change which happens in the society. In this case, as the paradigm of how to manage an organization which concerns with mass society has been changed, so the university has to follow this change also. They say that university has to implement the fundamental aspects of good governance namely transparancy, responsibility, effectiveness, accountability, law enforcement, and the participation of the stakeholders in decision making process as well as in policy runs by the university. If it is done, so it is hoped that mutual beliefs and mutual understanding as well as mutual honorus will emerge in the whole educational stakeholders sense to make the ouality of the university performances enhance optimally.